Analysis of the diversity of tick-borne viruses at the border areas in Liaoning Province, China - Bai, Yu; Li, Yang; Liu, Wenli; Li, Jing; Tian, Fengjuan; Liu, Lei; Han, Xiaohu; Tong, Yigang (Frontiers in Microbiology, 2023)
Ticks play a significant role in transmitting arboviruses, which pose a risk to human and animal health. The region of Liaoning Province, China, with abundant plant resources with multiple tick populations, has reported several tick-borne diseases. However, there remains a scarcity of research on the composition and evolution of the tick virome. In this study, we conducted the metagenomic analysis of 561 ticks in the border area of Liaoning Province in China and identified viruses related to known diseases in humans and animals, including severe fever with thrombocytopenia syndrome virus (SFTSV) and nairobi sheep disease virus (NSDV). Moreover, the groups of tick viruses were also closely related to the families of Flaviviridae, Parvoviridae, Phenuiviridae, and Rhabdoviridae. Notably, the Dabieshan tick virus (DBTV) of the family Phenuiviridae was prevalent in these ticks, with the minimum infection rate (MIR) of 9.09%, higher than previously reported in numerous provinces in China. In addition, sequences of tick-borne viruses of the family Rhabdoviridae have first been reported from the border area of Liaoning Province, China, after being described from Hubei Province, China. This research furthered the insight into pathogens carried by ticks in the northeastern border areas of China, offering epidemiological information for possible forthcoming outbreaks of infectious diseases. Meanwhile, we provided an essential reference for assessing the risk of tick bite infection in humans and animals, as well as for exploring into the evolution of the virus and the mechanisms of species transmission.